PENGARUH STRES KERJA DAN IKLIM ORGANISASI TERHADAP TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADAPERAWAT RS. X DI SURABAYA - Novy Fitria (STIE Mandala Jember, 2015)
The study aims to examine the effect of work stress and organization climate to the turnover intention with job satisfaction as an intervening variable. Conducted at hospital X in Surabaya, the study applies proportional random sampling in taking samples from 50 respondents. This research includes the study explanatory and confirmatory. The obtained data is analyzed using Partial Least Square (PLS) in SmartPLS program. The result shows that: there is a significant positive and non-direct effect between work stress and turnover intention through work satisfaction; there is a significant negative and non-direct effect between organization climate and turnover intention through work satisfaction; and work satisfaction can lower turnover intention.